2004
DOI: 10.1016/j.memsci.2003.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of adsorption–flocculation–microfiltration hybrid system in wastewater reuse

Abstract: Membrane hybrid systems are becoming increasingly important as cost effective solutions in wastewater treatment and reuse. The effects of pretreatment namely floating medium flocculation (FMF) and powdered activated carbon (PAC) adsorption on organic and phosphorus removal was studied. The FMF was found to increase the phosphorus removal up to 97%. This preflocculation improved the dissolved organic removal only marginally (from 20% to 40%) whilst the pretreatment of adsorption increased the organic removal to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Salts may have incorporated into the interior of the biocarbon and influenced development of internal porosity. Activation process also inhibits particle shrinkage and volume contraction (Guo et al, 2007). This result is in agreement with previous study where BET surface area of palm shells biocarbon (206 m 2 /g) is lower than activated palm shells biocarbon treated with H2SO4 (1014 m 2 /g) (Guo et al, 2005).…”
Section: Adsorption Of Methylene Bluesupporting
confidence: 92%
“…Salts may have incorporated into the interior of the biocarbon and influenced development of internal porosity. Activation process also inhibits particle shrinkage and volume contraction (Guo et al, 2007). This result is in agreement with previous study where BET surface area of palm shells biocarbon (206 m 2 /g) is lower than activated palm shells biocarbon treated with H2SO4 (1014 m 2 /g) (Guo et al, 2005).…”
Section: Adsorption Of Methylene Bluesupporting
confidence: 92%
“…The TMP stabilised at 0.1 bars at 10 LMH which indicated lower cake resistance and less membrane fouling with PAC addition, and showed that the SAMBR can be operated for some time at constant flux. Guo et al [29] have reported increases in filtration (permeate) flux of microfiltration by the incorporation of PAC as a pre-treatment method, where PAC adsorption led to a six times higher critical flux than without. The TMP increased to 0.25 bars only when the recycle flux was increased to 15 LMH, which shows that around 10 LMH was the critical flux in the presence of 1.67 g l -1 PAC under the given operating conditions, however, the TMP dropped back to a very low value when the flux was reduced to 10 LMH showing that the membrane fouling was reversible.…”
Section: Particle Size Distributionmentioning
confidence: 99%
“…Thus, there is a need to establish an integrated hybrid system incorporating immersed membranes with adsorption and fl occulation. A long-term study with immersed membrane/adsorption hybrid system showed a consistent and superior organic removal with practically no membrane fouling [4].…”
Section: Introductionmentioning
confidence: 91%
“…The organic matter corresponding with the MW fraction of 1510 Da, 1180 Da, 530 and 130 Da represents biopolymers (polysaccharides and proteins), fulvic acid, low MW acids (hydrolysates of humic substances), and amphiphilics, respectively [4,8]. Figure 4 shows the MWD of SWOM with and without prereatment.…”
Section: Molecular Weight Distribution (Mwd) After Different Pretreatmentioning
confidence: 99%
See 1 more Smart Citation